2004
DOI: 10.1002/ajim.20001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on diagnostic tests for work‐related hypersensitivity pneumonitis: Data from an outbreak of lung disease in metalworkers

Abstract: It appears that cigarette smoking can affect the physical examination findings, spirometry, and ESR changes associated with HP, making these tests less sensitive and specific, and potentially obscuring the diagnosis. Such changes may contribute to the apparent "protective" effect of smoking on the development of HP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(72 reference statements)
0
3
0
1
Order By: Relevance
“…Dangman KH et al. ( 49 ) implemented a retrospective study targeting metalworkers with HP, and researchers found that the development of hypersensitivity pneumonitis is forestalled in cigarette smokers. Kobayashi H et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dangman KH et al. ( 49 ) implemented a retrospective study targeting metalworkers with HP, and researchers found that the development of hypersensitivity pneumonitis is forestalled in cigarette smokers. Kobayashi H et al.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of smoking has been explained by a negative effect on the cells involved in antibody production and decreased B7 co-stimulatory molecule expression on alveolar macrophages of cigarette smokers [48,75]. However, other studies have suggested that despite a higher prevalence of precipitating antibodies and restrictive lung disease among non-smokers, smokers have a similarly decreased lung diffusion capacity and are more likely to develop insidious and chronic HP than non-smokers [86][87].…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Niezależnie o dylematów dotyczących udziału palenia papierosów w rozwoju włóknienia płuc, zaobserwowano, że nikotynizm wywiera ochronny wpływ na rozwój innych ILD, szczególnie chorób ziarniniakowych [10]. Świadczyć może o tym niewielki odsetek palaczy wśród chorych na alergiczne zapalenie pęcherzyków płucnych (AZPP) [11,12]. Badania eksperymentalne u zwierząt wykazały ochronny wpływ nikotyny na rozwój tej choroby [13].…”
unclassified